Analisis Pengambilan Keputusan dalam Kendala di Wisata Alam Kaliwungu Karawang Jawa Barat - Delia Karya; Khurfa Tusiva; Muhammad Yusuf Hanifan; Nazwa Putri Gunawan (Nawasena: Jurnal Ilmiah Pariwisata, 2025)
Kaliwungu nature tourism in Karawang, West Java, faces various constraints in management that impact strategic decision making. This study aims to analyze the main constraints that include the management of labor, capital, raw materials, and marketing. The study used a qualitative approach with an explanatory survey method, where data were collected through interviews, observation, and document analysis. The results show that labor management faces challenges in the form of dependence on labor from outside the region, which causes high operational costs. Capital management also requires adjustments to the Break Even Point (BEP) time from three to four years due to low levels of tourist visits. In terms of raw materials, inventory shortages often occur, affecting visitor satisfaction. On the marketing side, the utilization of digital media has not been optimal to attract tourists from outside the region. Further discussion underscores the importance of more efficient management strategies, including the development of local labor, strengthening digital marketing, and better raw material management. The practical implications of this research include the need for innovation in marketing strategies, improved service quality, as well as more planned resource management to increase the competitiveness of Kaliwungu tourism in both local and national markets. The conclusion of this study provides important insights for tourism managers to optimize their decision making and operational sustainability.